Comparison of vertical dimension of occlusion on edentulous and dentulous patients - Strajnić Ljiljana (Serbian Medical Society - Dental Section, Belgrade, 2004)
One of the existing methods for analysis of the vertical dimension of occlusion or occlusal face height is the cephalometric analysis of the distance from nasion to menton (N-Me). The vertical dimension of occlusion was measured in 30 lateral cephalometric radiographs of edentulous patients (experimental group), with models of complete dentures after clinical methods of determining the vertical and horizontal intermaxillary relation and 30 lateral cephalometric radiographs of participants with natural teeth (control group). The aims of the present study were: to analyse the vertical dimension of occlusion in participants with natural teeth skeletal class I, to cephalometrically evaluate the reconstructing vertical dimension of occlusion of edentulous patients skeletal class I , to compare examined variables between individuals with natural teeth and edentulous patients. The results indicated a remarkable correlation in the vertical dimension of occlusion established initially for the edentulous patients when compared with the measurements made for dentulous patients. The results showed the vertical dimension of occlusion span a range between 106,7 - 138 mm (X _ =122,24) in subjects with natural teeth. In edentulous patients the values of vertical dimension of occlusion span ranged between 109,8 - 141,6 mm (X _ =122,46). The vertical dimension of occlusion in male participans was increased in the group of persons with natural teeth as well as in edentulous patients. The results of t-test proved that there were no statistically significant differences in examined variables between persons with natural teeth and edentulous patients (p>0,01).